Evaluation and comparison of reading man flap based on different designs of angles and central axial lengths using finite element method - Ling Chen; Xin Yang; Yunshi Zhang; Long Zhang; Youchen Xia (Scientific Reports)
Abstract Different angles and central axis length combinations of the reading man flap were studied to determine the optimal angles and central axis length combinations for reducing the stress on the flap tip. First, different models and corresponding finite element models of flaps with different angles and central axial lengths were established by ANSYS software. Then, skin flap transfer was achieved through forced displacement, and the stress distributions of the flap with different angles and central axial lengths under different materials were obtained. Finally, the stress distributions of the flaps of each case were compared and analysed. The results shows: (1) The optimal angle and central axis for reducing the stress of the flap tip are 60° for the quadrangular flap, 45° for the triangular flap, with a 2 fold increase in length of the central axial relative to the diameter of the circular defects. (2) The quadrangular flap tip tends to have a greater possibility of complications than does the triangular flap tip. (3) The stress of the triangular flap tip is more sensitive to the angle and central axis length. (4) The stress of the flap tip in elderly people is greater than that in young people with the same design and position, which leads to greater possibility of complications at the flap tip in elderly patients than in young patients.